PENGARUH PUPUK KANDANG KAMBING DAN KCl TERHADAP HASIL TANAMAN BAWANG MERAH (Allium ascalonicum L.) PADA TANAH PEDZOLIK MERAH KUNING - Rubiah Sagita; Sri Mulyani (DINAMIKA PERTANIAN, 2024)
The study aims to investigate the interaction and primary effects of goat manure and KCl on shallots (Allium ascalonicum L.) grown in PMK soil. Conducted at the Experimental Farm of the Faculty of Agriculture, Riau Islamic University in Pekanbaru City, between December 2023 and February 2024, the research employed a Completely Randomized Design (CRD) with two factors. The first factor, goat manure, had four levels: 0, 1.5, 3, and 4.5 kg per plot. The second factor, KCl dosage, also had four levels: 0, 10, 20, and 30 g per plot, resulting in 16 treatment combinations with three replications. The parameters measured included plant height, harvest age, number of tubers per clump, tuber diameter, wet weight per clump, dry weight per clump, and tuber weight loss. The data were statistically analyzed, followed by further BNJ tests at the 5% significance level. The findings indicated that the interaction between goat manure and KCl had a significant effect on plant height, number of tubers per clump, wet weight of tubers per clump, and dry weight of tubers per clump. However, harvest age, tuber diameter, and tuber weight loss did not exhibit significant differences due to the interaction. Goat manure had a significant main effect on all parameters, with the optimal treatment being 4.5 kg/plot. Similarly, KCl also had a significant main effect on all observed parameters, with the best treatment being 30 g/plot.